Glutamine coated titanium for synergistic sonodynamic and photothermal on tumor therapy upon targeted delivery - Zhang, Lina; Zhu, Pengfeng; Wan, Ting; Wang, Huaiyan; Mao, Zhilei (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The application of titanium dioxide nanoparticles (TiO2 NPs) for cancer therapy has been studied for decades; however, the targeted delivery of TiO2 NPs to tumor tissues is challenging, and its efficiency needs to be improved. Method: In this study, we designed an oxygen-deficient TiO2-x coated with glutamine layer for targeted delivery, as well as the enhanced separation of electrons (e-) and holes (h+) following the joint application of sonodynamic therapy (SDT) and photothermal therapy (PTT). Results: This oxygen-deficient TiO2-x possesses relatively high photothermal and sonodynamic efficiency at the 1064 nm NIR-II bio-window. The GL-dependent design eased the penetration of the TiO2-x into the tumor tissues (approximately three-fold). The in vitro and in vivo tests showed that the SDT/PTT-based synergistic treatment achieved more optimized therapeutic effects than the sole use of either SDT or PTT. Conclusion: Our study provided a safety targeted delivery strategy, and enhanced the therapeutic efficiency of SDT/PTT synergistic treatment.